Granger & DeHart Building, 1916. - Gordon, John C. (photographer):::Creator::::::::::::
Granger & DeHart Building with primarily brick facade. Glass panel doors opens to metal balcony in center of upper floor. Ornate ornamentation adorns various sections of the building.